Type 1 sensitisation against a Steinernema feltiae product. (8th June 2012) - Thilsing, Trine; Sherson, David; Madsen, Anne Mette; Baelum, Jesper
Abstract : The use of biological control measures (biopesticides) is a widespread and fundamental technique for crop protection in greenhouses. Previous reports have documented allergic sensitisation against predatory mites, bacteria and fungi. Till now no cases of sensitisation against nematode products have been described. Two subjects working at a flower greenhouse were examined at the Department of Occupational and Environmental Health at Odense University Hospital. A histamine release test revealed positive reaction against a nematode product containing Steinernema feltiae, but negative reaction when testing formulation ingredients separately. Skin prick testing with samples containing S feltiae or mixed carrier medium, separately, revealed positive reactions in both subjects against S feltiae samples only. Skin prick testing among seven control subjects revealed no positive reactions. This is the first report indicating type 1 sensitivity against a S feltiae product. These findings point to the need for guidelines and preventive measures when handling biopesticide products and biopesticide-treated plants.